2018
DOI: 10.1259/bjr.20170874
|View full text |Cite
|
Sign up to set email alerts
|

Low tube voltage prospectively ECG-triggered coronary CT angiography: a systematic review of image quality and radiation dose

Abstract: This systematic review found that radiation doses could be reduced to a rate of 38 to 83% at 80 kVp, and 3 to 80% at 100 kVp without compromising the image quality. Advances in knowledge: The suggested appropriate scanning parameters and CM reduction methods can be used to help users in achieving diagnostic image quality with reduced radiation dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
(100 reference statements)
0
13
0
Order By: Relevance
“…Initially, many studies have attempted to reduce TID by adjusting the contrast concentration or volume, and they mostly use a low iodine delivery rate (IDR) which was between 1.08 and 1.70 gI•s -1 (6)(7)(8)(9)(10)(11)(12). IDR represents the rate at which iodine is delivered into the arterial system and is the main determinant of VCE in CCTA.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, many studies have attempted to reduce TID by adjusting the contrast concentration or volume, and they mostly use a low iodine delivery rate (IDR) which was between 1.08 and 1.70 gI•s -1 (6)(7)(8)(9)(10)(11)(12). IDR represents the rate at which iodine is delivered into the arterial system and is the main determinant of VCE in CCTA.…”
Section: Introductionmentioning
confidence: 99%
“…In the human body, iodine contrast agents are filtered by glomerulus but not absorbed by renal tubules. During the process of glomerular filtration, concentration in the kidney increases, which may lead to a series of adverse reactions, such as renal damage ( 20 ). Low contrast agent flow rate and low contrast agent dose usually reduce the enhancement density of coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that using 100 kV instead of 120 kV resulted in up to 38% reduction in radiation dose. Similar studies reported different amount of radiation dose reduction regarding scanner type, ECG gating technique, and range of applied tube current . Furthermore, we achieved 21% reduction in iodine intake through lowering the concentration of contrast media.…”
Section: Discussionmentioning
confidence: 99%